Organometallic Iridium(III) Complex Sensitized Ternary Hybrid Photocatalyst for CO2 to CO Conversion. Issue 59 (19th September 2019) - Kim, Pil Soo; Choi, Sunghan; Kim, So‐Yoen; Jo, Ju Hyoung; Lee, Yoon Seo; Kim, Bupmo; Kim, Wooyul; Choi, Wonyong; Kim, Chul Hoon; Son, Ho‐Jin; Pac, Chyongjin; Kang, Sang Ook
Abstract: A series of heteroleptic iridium(III) complexes functionalized with two phosphonic acid (−PO3 H2 ) groups ( dfppy IrP, ppy IrP, btp IrP, and piq IrP ) were prepared and anchored onto rhenium(I) catalyst (ReP)‐loaded TiO2 particles (TiO2 /ReP) to build up a new IrP ‐sensitized TiO2 photocatalyst system (IrP /TiO2 /ReP). The photosensitizing behavior of the IrP series was examined within the IrP /TiO2 /ReP platform for the photocatalytic conversion of CO2 into CO. The four IrP ‐based ternary hybrids showed increased conversion activity and durability than that of the corresponding homo‐ (IrP +ReP) and heterogeneous (IrP +TiO2 /ReP) mixed systems. Among the four IrP /TiO2 /ReP photocatalysts, the low‐energy‐light (>500 nm) activated piq IrP immobilized ternary system ( piq IrP /TiO2 /ReP) exhibited the most durable conversion activity, giving a turnover number of ≥730 for 170 h. A similar kinetic feature observed through time‐resolved photoluminescence measurements of both btp IrP /TiO2 and TiO2 ‐free btp IrP films suggests that the net electron flow in the ternary hybrid proceeds dominantly through a reductive quenching mechanism, unlike the oxidative quenching route of typical dye/TiO2 ‐based photolysis. Abstract : Electron transfer : An organometallic Ir III dye‐sensitized TiO2 hybrid exhibited efficient and steady photocatalytic activity, as a result of efficient photoelectron collection/transportation from the Ir III photosensitizer to the Re I catalytic site through the TiO2 semiconductor (see figure).